The Role of Mothers in Strengthening Household Economic Resilience Through MSMEs Toward Achieving SDGs - Hendra Hadiwijaya; Mirza Putri Andita; Umari Abdurrahim Abi Anwar (Penerbit Goodwood, 2026)
Purpose: This study examines the role of mothers in strengthening household economic resilience through their involvement in Micro, Small, and Medium Enterprises (MSMEs) in Banyuasin Regency and their contribution to achieving Sustainable Development Goals (SDGs) 5 and 8. Research Methodology: A quantitative approach was employed using a survey of 120 mothers who actively own and manage MSMEs in the beauty, food, handicraft, and service sectors in Indonesia. Data were collected through a structured questionnaire and analyzed using Variance-Based Structural Equation Modeling (VB-SEM) with the Partial Least Squares (PLS) technique. Results: The findings indicate that MSMEs have a strong and significant direct effect on household economic resilience (? = 0.738; T = 9.359). Mothers’ participation also directly influences household economic resilience (? = 0.179; T = 2.104) and significantly contributes to MSME development (? = 0.681; T = 13.017). Furthermore, mothers’ involvement indirectly enhances household economic resilience through MSMEs (? = 0.502; T = 8.216). Conclusions: Empowering mothers through MSME activities significantly strengthens household economic resilience, with MSMEs serving as important mediating mechanisms. Limitations: This study was limited to Banyuasin Regency, which may restrict the generalizability of the findings. Contributions: This study contributes to the Human Resource Management and women’s entrepreneurship literature by highlighting the strategic role of mothers in promoting family economic resilience and sustainable development.